Supercritical CO2 extraction of essential oil from jasmine flower and yield optimization - H. H., Rassem; Nour, A. H.; R. M., Yunus; Y. H., Zaki; H. S., Abdlrhman (2018)
Supercritical liquid extraction (SFE) is an innovation that permits extraction of an extensive variety of different composition from an assortment of plant grids. Extraction of essential oil from Jasmine flower was done by used Supercritical CO2 tentatively and the impact of working parameters, for example, pressure and temperature on the separating procedure were explored, thinking about three distinct esteems for every parameter (100 and 300 bar and 300 and 350 Kelvin for weight and temperature, individually). The extraction procedure was upgraded by methods for a trial configuration utilizing the measurable programming, Design Expert 7.1.6. A moment arrange Multiple was utilized to obvious the oil recuperation yield utilizing the reaction surface approach RSM and the acquired outcomes were near the test esteems with a relationship factor of 12.18, showing again the unwavering quality of this procedure. GC-MS examinations were done on tests got at the ideal conditions (200 bar and 325 K). The typical likelihood plan of the residuals and the plot of the residue against the anticipated reaction to Jasmine bloom oil yield was being. The examinations of the acquired reaction surface demonstrated that pressure had the most critical impact on the oil extraction yield, through the quadratic and straight terms. The temperature moderately affected the oil yield rather through its square term, which demonstrated a low importance oppositely to the straight and cooperation terms.